Training on Making Creative Thinking Rubrics for Junior High School Teachers in Sarolangun Jambi - Silvia Fitriani; Rofii, Afif (Jurnal Pengabdian Masyarakat Ilmu Pendidikan, 2024)
The implementation of the Community Service Program (PkM) aims to improve the competency of junior high school teachers in Sarolangun, Jambi. By holding workshops, the training activities were attended by 25 junior high school teachers. The training process consists of three stages: introduction to the material, training, and evaluation for making creative thinking assessment rubrics. The expected achievement from implementing this PkM is increasing the knowledge and skills of junior high school teachers in designing assessment rubrics that support the development of student's creative thinking. The training results showed that the training participants experienced an increase in their understanding of creating creative thinking assessment rubrics. The implication achieved from successfully implementing PkM is improving the quality of learning in junior high schools in Sarolangun, Jambi. Teachers who have increased their competence in designing creative thinking assessment rubrics are expected to be able to apply assessment methods that are more holistic and relevant to students' thinking abilities. Apart from that, it is also hoped that this increase will positively impact the development of students' creativity and critical thinking abilities at the school. Thus, the implementation of PkM has the potential to improve individual teacher competence and can contribute more broadly to improving the quality of education in the region.